2004
DOI: 10.1016/j.burns.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of essential oils on methicillin-resistant Staphylococcus aureus using a dressing model

Abstract: Patchouli, tea tree, geranium, lavender essential oils and Citricidal (grapefruit seed extract) were used singly and in combination to assess their anti-bacterial activity against three strains of Staphylococcus aureus: Oxford S. aureus NCTC 6571 (Oxford strain), Epidemic methicillin-resistant S. aureus (EMRSA 15) and MRSA (untypable). The individual essential oils, extracts and combinations were impregnated into filter paper discs and placed on the surface of agar plates, pre-seeded with the appropriate strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 12 publications
(12 reference statements)
7
84
0
Order By: Relevance
“…The obtained results are in agreement with a previous study of Edwards-Jones et al, where the antibacterial activity of pure LO against S. aureus has been demonstrated by detecting inhibition zones of approximately 20 mm in diameter. 36 The main components of LO, linalool and linalyl acetate, are responsible for the antibacterial properties of this essential oil, 50,51, 52 with linalool being more effective than linalyl acetate. 52 Furthermore, LO contains terpinen-4-ol that, like linalool, exhibits antimicrobial activity.…”
Section: Antibacterial Activity Of the Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results are in agreement with a previous study of Edwards-Jones et al, where the antibacterial activity of pure LO against S. aureus has been demonstrated by detecting inhibition zones of approximately 20 mm in diameter. 36 The main components of LO, linalool and linalyl acetate, are responsible for the antibacterial properties of this essential oil, 50,51, 52 with linalool being more effective than linalyl acetate. 52 Furthermore, LO contains terpinen-4-ol that, like linalool, exhibits antimicrobial activity.…”
Section: Antibacterial Activity Of the Nanofibersmentioning
confidence: 99%
“…32,33 Moreover, LO possesses antibacterial and antifungal properties, 28,34,35 pointing out its efficacy against Staphylococcus aureus that is the bacterium mostly responsible for burn wound infections. 36 Electrospun nanofibers of Polyacrylonitrile (PAN) containing lavender oil have been recently developed for antibacterial and drug delivery applications. 37 Although both inorganic and organic antiseptic agents have shown a certain degree of success for various medical applications, the use of all-natural medicinal extracts, such as LO, can further boost pharmaceutical applications and improve patient recovery and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Aconitum is proven to be helpful in all kinds of infection including MRSA. In homeopathic doses, belladonna remedy (extremely small doses) is also used to cure the red skin, often associated with the infections [27].…”
Section: Alternative Remediesmentioning
confidence: 99%
“…are exposed to a citrus EO vapour, morphological changes also happen, mutually with an raise in cell permeability, loss of intracellular ATP and a reduce in intracellular pH (Fisher and Phillips, 2009). When bacteria were exposed to the vapours of EO, the inhibitory actions were obviously diverse from those established by direct contact (Edwards-Jones et al, 2004). A study carried out by (Goni et al, 2009) revealed that inhibitory effect of mixture of clove and cinnamon EO in vapour phase showed superior antibacterial with fewer active concentrations in the vapor phase compared to liquid phase.…”
Section: Table 2 the Main Components Identified In The Essential Oilmentioning
confidence: 99%